„Był tutaj” : O Tryptyku żałobnym Anny Frajlich .......... 199 - Paliwoda, Agata (Tu jestem / zamieszkuję własne życie : studia i szkice o twórczości Anny Frajlich, 2018)
“HE WAS HERE”: ABOUT ANNA FRAJLICH’S “FUNERAL TRIPTYCH”The article analyses Tryptyk żalobny [‘Funeral Triptych’] by Anna Frajlich. The work, dedicated to Jerzy Szczygieł (former boss, friend, or even the poet’s role model), is a poetic account of dealing with the loss of someone close. References to tradition, including antiquity, Old Testament, Jan Kochanowski’s Treny [‘Lamentations’] and baroque metaphysical poetry, serve - like other similar intertextual references in funeral literature - to demonstrate (somewhat comfortingly) that fear of death and helplessness in the face of it are universal and eternal, but so is the uncompromising attitude in attempting to explore its mystery.